2012
DOI: 10.1039/c2ob26442k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of the [3 + 2] cycloaddition of carbonyl ylides with alkynes

Abstract: The [3 + 2] cycloaddition reaction between carbonyl ylides generated from epoxides and alkynes ( phenylacetylene, methyl propiolate, methyl but-2-ynoate and methyl 3-phenylpropiolate) to give substituted 2,5-dihydrofurans was investigated. The effect of indium(III) chloride on the outcome of the reaction was studied in the case of phenylacetylene and methyl propiolate. The thermal reaction between the carbonyl ylide coming from 2,2-dicyano-3-phenyloxirane and both methyl propiolate and methyl but-2-ynoate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…In this situation, the dipolarophile thus played the role of the electron donor, in contrast with the electron demand expected from the MO energies, but consistently with the potential competition between the two processes, as explained above. The fact that steps b and c were not initiated at the TS was fully in line with the absence of charge transfer at that point, as proposed from the geometry and the literature. , We note that a similar description was obtained in the case of model nitronate 8 (Table , channel 8, and Figure FS5, Supporting Information) and for the reaction involving vinylether 2 (Table , channel 3, and Figure FS6, Supporting Information), except that for the reaction coordinate values and for the details of step b, as in these two cases, no enrichment of the LP (N2) was observed. These results can also be compared to the description of the 1,3-dipolar cycloaddition between fulminic acid and acetylene published by Polo et al for which similar LP (N), B (C–C), and B (C–O) formations were also observed, but for which the B (C–N) and B (C–C) bond breaking were found to be monotonous during the reaction course, with no abrupt B (C–C) formation step.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In this situation, the dipolarophile thus played the role of the electron donor, in contrast with the electron demand expected from the MO energies, but consistently with the potential competition between the two processes, as explained above. The fact that steps b and c were not initiated at the TS was fully in line with the absence of charge transfer at that point, as proposed from the geometry and the literature. , We note that a similar description was obtained in the case of model nitronate 8 (Table , channel 8, and Figure FS5, Supporting Information) and for the reaction involving vinylether 2 (Table , channel 3, and Figure FS6, Supporting Information), except that for the reaction coordinate values and for the details of step b, as in these two cases, no enrichment of the LP (N2) was observed. These results can also be compared to the description of the 1,3-dipolar cycloaddition between fulminic acid and acetylene published by Polo et al for which similar LP (N), B (C–C), and B (C–O) formations were also observed, but for which the B (C–N) and B (C–C) bond breaking were found to be monotonous during the reaction course, with no abrupt B (C–C) formation step.…”
Section: Resultssupporting
confidence: 84%
“…The reaction was found to proceed through a concerted mechanism, and the TS were slightly asynchronous (Figure ). These structural features were proposed to be associated with a small charge transfer at the TS and with nonpolar mechanisms …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these calculations will show that the sole indicator of the HOMO–LUMO gap cannot account for the difference in chemoselectivities caused by different Lewis acid catalysts, especially for C–O selectivity. For those complicated reactions beyond the control of a simple FMO picture, density functional theory (DFT) was widely used to gain a more quantitative picture of reaction paths and corresponding activation energy barriers . The catalytic effects of noble metals (for instance, the complexes of Rh, Pt, et al) and Lewis acids (such as the metallic salts and BF 3 ) have been addressed theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…7 The synthesis of such compounds has been the subject of several reviews which demonstrate the high importance of this class of compounds. [8][9][10][11][12][13] Considering the importance of these compounds, many methods for the synthesis of these derivatives have been reported successively. The conventional synthesis imidazoles, 17 1,3-oxathioles 18 and condensed imidazolo and thiazolo derivatives, 19 because of their multifunctional structure.…”
Section: Introductionmentioning
confidence: 99%